Students Online English Club of STITM Ngawi In Pandemic Era: A Learning Challenge - Nining Wulandari (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
At this time the world has been shocked by the plague that affects all levels of society, in this case the world of education has the most real impact. The world of education, especially universities where students are very active are forced to study independently from home so that there are many complaints and other negative impacts. In order the lecture also have many problems faced these new method on learning from home. Here the researcher teaches English, EFL instruction shows different paradigm during Covid-19 Pandemic. Face to face or conventional English study club classroom sessions in University has transformed into Learn from Home (LFH). In addition, The Ministry of Education and Culture has issued a circular Number 15 in 2020 to regulate LFH in a response to the raise of Covid- 19 sufferers and victims. This study was to describe challenges faced by the lecturer and students of university in online TEFL, especially for the second grade of university students of STITM Ngawi. This was a case study by means of direct observation towards online English club classroom sessions implementing in a rural public university level in Mantingan regency, East Java province, Indonesia; documentations on their works and projects; and interview. The result shows that the challenges are students’ economic background affecting their readiness in preparing gadgets and quota to get involved in online learning, internet connection, time, supplementary materials, and heterogeneous students’ capability.